Penurunan Kadar Gula Darah Pasien DM Tipe 2 dengan Aktivitas Fisik - I Made Sundayana; I Dewa Ayu Rismayanti; Ida Ayu Putu Desta Candra Devi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between physical activity and blood glucose levels in patients with type 2 diabetes. The research design used was a descriptive correlation with a cross-sectional approach. The results of the univariate analysis showed that the majority of respondents had moderate activity, as many as 19 people (43.2%), and the majority of respondents had poor blood sugar levels, namely 21 people (47.7%). The results of the bivariate analysis showed that p-value = 0.000 <0.05 with a correlation coefficient (r = 0.756). In conclusion, there is a relationship between physical activity and blood sugar levels in Type 2 DM patients. Keywords: Physical Activity, Type 2 Diabetes Mellitus, Blood Glucose